PROCESS FORMULATION AND USAGE OF CASTOR SEED OIL AND POLYVINYL ACETATE ADMIXTURE IN THE MANUFACTURING OF EMULSION PAINT - Ugbune, Ufuoma; Okhuarobo, Osamwen L. (FUDMA Journal of Sciences, 2023)
Paints are widely used for surface coating, they are made with combinations of different raw materials, for example polyvinyl acetate. The cost of this raw material is increasing daily in Nigeria due higher exchange rate of dollar to naira coupled with an increasing number of entrepreneurs using this material for paint production daily. This raw material is synthetic and not eco-friendly. Therefore, this research seeks to fill this gap by using natural material (castor seed oil) that is cheap and eco-friendly as combinatorial with polyvinyl acetate. Castor seed oil used for this research was sourced from a local market in Delta State. Castor seed oil was extracted using solvent extraction. Paint was produced using four different formulations; Paint produced was characterized using ASTM method. Results obtained from the work showed 43.5 yield of castor seed oil, results of opacity, viscosity, specific gravity, drying time and pH are in the range of 9.5-22, 0.92-0.94,1.01-1.15 gcm3, 25-30 minutes, 7.9-8.6 respectively. The combination of 60% Polyvinyl acetate to 40% Castor seed oil was more effective for paint production due  to its low viscosity ( 0.920C) and high specific density  (1.15 kg/L). Therefore, 60% Polyvinyl acetate to 40% Castor seed oil combinatorial is recommended for paint production for economic and environmental gain
Keywords: Paint; polyvinyl acetate; castor seed oil